2016
DOI: 10.1038/cdd.2016.89
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin 1 protects pancreatic β-cells from lipotoxicity via the PERK–NRF2 pathway

Abstract: The failure of β-cells has a central role in the pathogenesis of type 2 diabetes, and the identification of novel approaches to improve functional β-cell mass is essential to prevent/revert the disease. Here we show a critical novel role for thrombospondin 1 (THBS1) in β-cell survival during lipotoxic stress in rat, mouse and human models. THBS1 acts from within the endoplasmic reticulum to activate PERK and NRF2 and induce a protective antioxidant defense response against palmitate. Prolonged palmitate exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 60 publications
(83 reference statements)
2
44
0
1
Order By: Relevance
“…This raises the alternative possibility that the PKR-like endoplasmic reticulum kinase (PERK) initiating axis of UPR was specifically inactivated by TFG deficiency, despite the activating transcription factor-6 (ATF6) and inositol requiring enzyme 1 (IRE1) axes being activated. Nrf2 activation is suggested to be downstream from PERK 25 . However, as discussed above, Nrf2 is not activated instead being downregulated in TFG-deficient islets, again showing no activation of the PERK axis of the UPR under TFG-deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the alternative possibility that the PKR-like endoplasmic reticulum kinase (PERK) initiating axis of UPR was specifically inactivated by TFG deficiency, despite the activating transcription factor-6 (ATF6) and inositol requiring enzyme 1 (IRE1) axes being activated. Nrf2 activation is suggested to be downstream from PERK 25 . However, as discussed above, Nrf2 is not activated instead being downregulated in TFG-deficient islets, again showing no activation of the PERK axis of the UPR under TFG-deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The multimeric Ca 2ϩ -binding glycoprotein thrombospondin 1 (THBS1) protects cardiomyocytes against ER stress via activation of ATF6 and downstream chaperones (12). We have shown recently that THBS1 protects human and rodent ␤-cells from palmitate-induced apoptosis (13). Different from cardiomyocytes, however, this takes place through activation of the ER stress transducer protein kinase R-like endoplasmic reticulum kinase (PERK) and the downstream transcription factor NRF2, increasing the ␤-cell capacity to withstand oxidative stress induced by saturated fatty acids (13).…”
mentioning
confidence: 99%
“…Here we tested whether THBS1 is equally beneficial to rodent and human ␤-cells exposed to cytokines or chemically induced ER stress. THBS1 was clearly protective, but this was mediated by a different mechanism compared with protection against lipotoxic ␤-cell demise (13) or cardiomyopathy (12); namely, through induction of the mesencephalic astrocyte-derived neutrotrophic factor (MANF). This raises the intriguing possibility that the multifunctional protein THBS1 changes roles and/or partner affinities in a cell-or stress-specific manner, as suggested recently for other complex biological systems (14).…”
mentioning
confidence: 99%
“…The capacity of beta cells to handle nitrosative and oxidative stress is regulated in part by nuclear factor erythroid 2-related factor 2 (NRF2) [28], a transcription factor that controls the expression of antioxidant genes (particularly those related to the glutathione pathway). Similar to beta cell UBC9, NRF2 expression in beta cells protects against iNOS-induced islet dysfunction and glucose intolerance [28], and against palmitate-induced oxidative stress [29]. He et al nicely link UBC9 and NRF2 by showing that SUMOylation regulates the nuclear localisation and stability of NRF2, likely by preventing its ubiquitin-mediated proteasomal degradation.…”
Section: Downstream Sumo-dependent Mechanisms In Isletsmentioning
confidence: 99%
“…The ability of high glucose culture, presumably a state of oxidative stress, to upregulate SUMO transcripts and UBC9 protein hints that this could be a feed-forward mechanism [20]. Also, recent work has suggested that palmitate-induced oxidative stress transiently increases NRF2 protein levels [29], although it is not yet known whether this results from a SUMO-dependent stabilisation.…”
Section: Redox and Oxidative Stress Interactions With Islet Sumoylationmentioning
confidence: 99%